The Moderating Impact of Social Media Use on Culturally Sustainable Tourism from the Perspective of the Theory of Planned Behaviour - Ambara, Riqi Dwi; Arifin, Zainul; Mawardi, Mukhammad Kholid (Graduate School, Universitas Brawijaya, 2025)
This research analyzes the Theory of Planned Behaviour (TPB) cultural tourism model to understand key factors for tourists. The scope includes an analysis of the influence of social media use on the TPB model of cultural tourism. A review of previous research shows that the TPB model has had a positive impact and has helped investigate tourist behavior. Therefore, this research aims to analyze how attitudes, perceived behavioral control, and subjective norms from the TPB model influence tourist behavior towards cultural tourism in Sade Cultural Village, Central Lombok, West Nusa Tenggara, from the Theory of Planned Behavior perspective. A total of 166 tourist respondents were sampled. This research uses quantitative methods. This research shows that the Theory of Planned Behavior model (attitude, subjective norms, and behavioral control) directly influences visiting intentions. Intensity of social media use has a moderate influence on subjective norms and the relationship between visiting intentions. Intensity of social media use also has a moderate influence on behavioral control and the relationship between visiting intentions. Keywords: Attitude, Behavior Control, Social media, Intention to visit, Subjective norms, Theory of Planned Behaviour.